The Determinant of the Prothrombin Time in Normal Human Plasma - Quick, Armand J. (Thrombosis and Haemostasis, 1958)
Normal adult human plasma has a constant prothrombin time when determined under standardized conditions and with carefully prepared reagents. An explanation for this constancy is offered; namely, that a plasma factor, designated as “prothrombin time fixing agent” (PTFA), is responsible for maintaining a constant fraction of the total prothrombin in the active state. This fraction is measured quantitatively by the prothrombin time, while the inactive prothrombin or prothrombinogen, has no influence on the test. The concentration of PTFA is fixed by heredity and appears to be a dominant. The results of studies on two subjects, one with true hypoprothrombinemia, the other with a prolonged prothrombin time but a normal total prothrombin and no deficiency of accessory prothrombin factors are reported and interpreted according to this hypothesis. A deficiency of PTFA can be differentiated from all other known hypoprothrombinemic states by observing a prolonged prothrombin time when mixing the plasma with an equal volume of fresh normal plasma.